Testing and Evaluation of Student Achievement in Canada. Bibliographies in Education. No. 80 = Administration de tests et evaluation du rendement des eleves au Canada. Bibliographies en education No. 80 - Canadian Teachers' Federation, Ottawa (Ontario).; Canadian Teachers' Federation, Ottawa (Ontario). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
This annotated bibliography draws together references in English and French to Canadian materials on testing and evaluation of student achievement. The bibliography includes books, journal articles, tests, publications, and manuals, published between 1976 and 1984. Entries are arranged alphabetically under such topical subheadings as: (1) general works; (2) development of testing instruments; (3) diagnostic testing; (4) district-wide testing programs; (5) factors related to achievement scores; (6) fairness in testing; (7) grade inflation; (8) item pools and testing services; (9) longitudinal evaluation of achievement; (10) prediction of achievement; (11) provincial, national, and international testing programs; (12) standardized tests; (13) teacher manuals; (14) teachers' student evaluation procedures; (15) test administration and scoring; (16) test characteristics; (17) test interpretation; and (18) test results for specific content areas. (CB)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Annotated Bibliographies; Educational Testing; Foreign Countries; Student Evaluation; Canada; Reference Materials, Bibliographies